Status prawny wybranych rodzajów biomasy rolniczej - kilka uwag w świetle nowego prawodawstwa - Błażejewska, Kamila (Wydawnictwo Naukowe UAM, 2013)
Legal status of selected types of agricultural biomass – some remarks in light of the new legislation S u m m a r y The purpose of this paper is to clarify certain issues related to the legal status of individual types of agricultural biomass. The analysis of the subject in question allows to conclude that exclusion of safe agricultural biomass from the rigid regime that governs wastemanagement simplifies the procedures regarding handling substances suitable for bioenergy production. A certain drawback of the current regulation is the lack of an unambiguously definition of the type of installations in which so exempted agricultural biomass may be used. Although the new law on waste management clarifies certain issues connected with the methods of agricultural biomass recovery, there remain concerns that postfermentation pulp has been given a ‘waste’ status. Instead of determining the ways in which the pulp may be processed to be subsequently utilized as a fertiliser, the Polish legislator chose to regulate this issue by placing it under regulations adopted for waste management. This means that an agricultural biogas producer may not, in principle, release post-fermentation pulp to entities which are not holders of waste recovery licenses.

Lo status giuridico dei tipi di biomasse agricole scelti – alcune osservazioni alla luce della nuova legislazione R i a s s u n t o Lo scopo delle considerazioni è quello di chiarire alcune questioni legate alla determinazione dello status giuridico dei vari tipi di biomasse agricole. L’analisi svolta permette di far notare che l’esclusione di biomassa agricola, le cui risorse sono considerate sicure, dal rigido regime di gestione dei rifiuti, costituisce una semplificazione delle procedure di gestione di sostanze adatte alla produzione di bioenergia. Una certa manchevolezza è costituita dall’ambiguità nel determinare i tipi di impianti nei quali può essere utilizzata la biomassa agricola beneficiante della suddetta esclusione. Grazie alla nuova legge sui rifiuti sono state chiarite anche alcune questioni legate ai metodi di recupero della biomasa agricola. Numerosi dubbi vengono tuttavia sollevati dall’assegnazione dello status di rifiuto alla polpa post-fermentazione. Invece di stabilire le regole di trattamento Della polpa post-fermentazione al fine di “recuperarla” per il suo utilizzo come fertilizzante, il legislatore polacco si è limitato alla regolazione di queste questioni ricorrendo alle norme dell’ambito della gestione dei rifiuti. Ciò significa che il produttore di biogas agricolo, secondo la regola, non può passare la polpa post-fermentazione ai soggetti non autorizzati al recupero dei rifiuti.